EARLY SUPERHUMPS IN THE "KING OF THE SUPEROUTBURSTS" SYSTEM WZ SGE - I. L Andronov; A. V. Yushchenko; P. G.. Niarchos; K. Gazeas (Odessa Astronomical Publications, 2017)
Time series analysis of 6 nights of CCD observations of WZ Sge after it's unexpected superoutburst on July 23, 2001 has shown highly asymmetric periodic variations with a period 0.d0566513(22), full amplitude 0.m218(4) and a very high asymmetry M - m = 0.670(9); a secondary minimum 0.38P after the main one. The initial epochs are Tmax = BJD2452118.7483(3) and Tmin = BJD52118.7670(2): The characteristics of the phase light curve are listed. In addition, we have found superhumps with a semi-amplitude of 0.m021(2) and an ephemeris Tmax,sh = BJD2452117.6830(8) + 0.d057435(45) E. Other peaks at 21 and 25 minutes possibly correspond to quasi-periodic oscillations with an effective semi-amplitude of 0.m014.